‘I am because you are’: Community support as a bridge to mental wellbeing for resettled African refugee women living in Rhode Island - Kira DiClemente-Bosco; Aline Binyungu; Clement Shabani; Jennifer A. Pellowski; Don Operario; Nicole Nugent; Abigail Harrison (Global Public Health)
African refugee women resettled in the United States are exposed to multiple risk factors for poor mental health. Currently, no comprehensive framework exists on which to guide mental health interventions specific to this population. Through a community-based participatory research partnership, we interviewed N = 15 resettled African refugees living in Rhode Island. Here we (1) describe how meanings of mental health within the African refugee community vary from US understandings of PTSD, depression, and anxiety and (2) generate a framework revealing how mental health among participants results from interactions between social support, African sociocultural norms, and US norms and systems. Multiple barriers and facilitators of mental wellbeing lie at the intersections of these three primary concepts. We recommend that public health and medicine leverage the strength of existing community networks and organisations to address the heavy burden of poor mental health among resettled African refugee women.